Upaya Paksa terhadap Pejabat yang Tidak Melakukan Putusan Pengadilan Tata Usaha Negara Denpasar - I Wayan Dedy Cahya Pratama; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2020)
The discussion in the writing of this thesis is a problem related to forced efforts as regulated in article 116 where in this article forced efforts (Dwangsom) are regulated. The purpose of implementing compulsory measures so that the decisions issued are carried out by those concerned. This study aims to determine the mechanism of forced attempts to officials who do not carry out the TUN Judicial Decision and to find out the obstacles to forced attempts against the TUN Judicial Decision. Normative legal research is used as a research method, which is a stage to find legal regulations, legal principles in order to answer the contents of the law in this thesis with a statutory approach, legal theory and a conceptual approach. Primary and secondary sources of legal materials are then analyzed to obtain conclusions and suggestions. The results showed that the efforts to force the decision, namely Dwangsom and administrative sanctions at the PTUN which had been incracht could not be implemented optimally. The obstacle in forced efforts related to the execution of the PTUN Decision is that there is no special agency tasked with implementing the decision, therefore the government has revised the PTUN Law and provisions relating to Forced Efforts issued by the Supreme Court so that it can be applied by the PTUN judge so that it can be applied and implemented optimally.